Civil engineer's reference book - Blake, L. S. 1925- (Butterworth-Heinemann, 1994)
This fourth edition has been completely rewritten and updated. Now with 20 interactive graphs and 2 interactive tables It provides a concise and comprehensive survey of the fundamentals, theory and current practice in the many branches of civil engineering, giving state-of-the-art information and practical guidance for both student and practicing civil engineers. --